A statistical analysis on Heavenly Diapers, Inc. - Cando, Kim E.; Pe, Jonna; Tappa, Milette (Diliman, Quezon City College of Engineering, 2002)
Heavenly Diapers Inc. is a partnership company that manufactures disposable baby diapers. It is a medium-sized company located at Malabon, Metro Manila. It has been producing economy diapers for two years now. This study focuses on the production and quality assurance departments of the company. It aims to apply the statistical tools and techniques learned in IE28. The proponents are able to identify potential problem areas and key process parameters of the product. Three major problems of the product are determined with respect to its frequency and probability of rejection. These include short tab which comprises 36.170 percent, weak adhesiveness of the glue which makes up 25.532 percent, and diaper weight, which consist 21.277 percent, of the overall rejection. In-depth analysis of these problems revealed glue machine temperature as the cause of weak adhesiveness, pulp feed as the cause of improper weight, and pressure as the cause of short tabs. The proponents validated these by conducting several tests of hypotheses using runs test, sign test, goodness of fit, analysis of variance through two factor analysis, Duncan's Multiple Range Test, graphical comparison of means, and residual analysis. Results showed that only roll pressure A have a significant effect on short tab, only pulp feed 2 has an effect on diaper weight, and the best range for the temperature setting of the glue machine was determined, which is the 150-165 degrees Celcius range. The proponents recommend the use of the 155 to 165 degrees Celcius setting for the temperature in order to enhance adhesiveness. The best range for pulp feed 2 is 170-175 percent speed setting to attain the company's targeted diaper weight. The pressure setting of 25-30 kiloPascals for pressure A is recommended to achieve the best tab lengths. On the other hand, the 20-25 kiloPascal for pressure A and 70-80 kiloPascal range for pressure B must be avoided in order to minimize variances in the tabs. Increase in the pulp feed, specifically pulp feed 2, should also be avoided in order to minimize variances in the weight of the disposable diaper.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 28 : Statistical Analysis for Industrial Engineering
Keywords: Statistics